Nerve Conduction Study in Bell’s Palsy - Shah, Sanjib Kumar; Kothari, R. P.; Bassi, S. D. (Journal of Nepalgunj Medical College, 2017)
Background: Nerve conduction study (NCS) is an important electrophysiological tool that can be used for the measurement of the latency and amplitude of the facial nerve. The NCS helps in predicting the prognosis of patients with Bell's palsy. Evaluation of NCS of patients with Bell's palsy may have contribution in counselling and management of the patient. Objective: The study was aimed to study the state of nerve damage in patients with Bell's palsy. Methods: The latency and amplitude of facial nerve stimulating bilateral Orbicularis Oculi and Orbicularis Oris muscles were assessed and noted in 24 patients of Bell's palsy. Results: 15(62.5%) of the patients had significant axonal injury affecting one side and only 1(4.16%) patient had demyelinating injury. The total of 8(33.33%) patients had insignificant axonal injury of the facial nerve in comparision with the normal side. Conclusions: Nerve conduction study shows predominant axonal type of facial nerve injury in patients with Bell's palsy and hence provides valuable information regarding the prognosis and the state of nerve damage in patients with Bell's palsy.